PAI Learning Model Based on Games Based Learning as an Interesting Learning Media for Students - Muis, Muhammad Aufa; Mardiana, Mardiana; Putri, Nurusyakira; Basir, Abdul; Barokah, Fitri (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2022)
This research aims to describe and explore the PAI Learning Model Based on Games Based Learning as an interesting learning media for students. This learning design is expected to increase teachers understanding of interesting learning concepts, mastery of moral values and active involvement of students in applying religious teachings and enjoyable learning in everyday life. Educational games based learning media is used as the main framework in designing and implementing learning that is specifically designed with the aim of educating and teaching certain concepts. This type of learning media utilizes games elements to create an interactive learning experience. Qualitative research methods are used to collect data through interview observation and documentation analysis using library research methods in processing the data and information needed. The conclusions of this research provide a clear understanding an providing for further development in increasing creativity in the learning process.